The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/dth.13257
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional injection of measles, mumps, and rubella vaccine versus cryotherapy in treatment of warts: A randomized controlled trial

Abstract: Cutaneous warts are benign hyperkeratotic papillomas resulting from infection by human papillomavirus (HPV). Cryotherapy is a known method for warts treatment. Immunotherapy stimulates HPV recognition by the immune system; this helps resolution of warts. To determine the efficacy of intralesional immunotherapy with measles, mumps, and rubella (MMR) vaccine versus cryotherapy in the treatment of patients with multiple common and plantar warts. Forty‐eight patients with multiple common and plantar warts were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 21 publications
2
12
4
Order By: Relevance
“…When comparing the efficacy of the MMR vaccine in the treatment of common warts, our study reported 67.7% complete response which was higher than that reported by Na et al 18 (47.6%) and Dhope et al 19 (65%). Meanwhile, our results were lower than those reported by Abdelmaguid et al 20 (70%), Nofal and Nofal 21 (81.4%), and Chauhan et al 22 (82.4%).…”
Section: Discussioncontrasting
confidence: 88%
“…When comparing the efficacy of the MMR vaccine in the treatment of common warts, our study reported 67.7% complete response which was higher than that reported by Na et al 18 (47.6%) and Dhope et al 19 (65%). Meanwhile, our results were lower than those reported by Abdelmaguid et al 20 (70%), Nofal and Nofal 21 (81.4%), and Chauhan et al 22 (82.4%).…”
Section: Discussioncontrasting
confidence: 88%
“…Regarding side effects in Group B, this study showed that pain on the day of injection occurred in only 16.7% of patients in Group B. Their pain was tolerable and did not affect the compliance of patients to continue the treatment protocol; this was in agreement with several previous studies (9,11,23,25). In our study, flu-like symptoms were not reported in Group B, and this was in agreement with the findings by Na et al (21).…”
Section: Discussionsupporting
confidence: 93%
“…In a recent study, Abd El-Magiud et al tested MMR vaccine versus cryotherapy for treating common and plantar warts, and they achieved a 70% cure in the MMR group with a 0.5 ml intralesional vaccine injection, biweekly for only three sessions (25). It should be taken into consideration that their patients in the MMR group included patients with common warts in addition to those with plantar ones (50% for each), whereby common warts are thought to be more readily responsive to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our observation, pain and flu like symptoms are the most common complications reported by others. [7][8][9][10][11][12][13][14]16 In our study, in Group B, Grade IV was noted in 60% patients while Grade III, Grade II and Grade I improvement was noted in 16%, 16% and 8% patients respectively. These findings are in agreement with previous studies.…”
Section: Discussionmentioning
confidence: 66%
“…10 However, on further evaluation by Shaheen et al (2015) who compared MMR with PPD, they found MMR to be better than PPD, with 60% response in the PPD group and 80% in the MMR group. 11 The efficacy of MMR vaccine in warts was further strengthened by reports of Shah et al (2016), 12 Dhope et al, (2017) 13 and Pushpendra Singh et al (2019) 14 who reported complete response in 72%., 65% and 82.4% patients respectively.…”
Section: Discussionmentioning
confidence: 96%